Prevalence of wasting and associated factors among children aged 6–59 months in Habro district, Eastern Ethiopia: a cross-sectional study - Tilahun, Sileshi; Roba, Kedir Teji; Roba, Hirbo Shore; Nure, Jemal Ahmed; Sosengo, Teshome; Ayele, Behailu Hawulte; Maruta, Melat B.; Debella, Adera; Eyeberu, Addis; Mussa, Ibsa (Frontiers in Nutrition, 2024)
Background: Globally, five million children under the age of five perished in 2021. Asia and African countries contributed 69% and 27.2% of wasting, respectively. In Ethiopia, children under-5 years is 10.1% (901), of which 8.1% (632) had moderate wasting and 3.0% (269) had severe wasting. As a result, the purpose of this study was to assess the prevalence of wasting and its associated factors among children between the ages of 6 and 59 months in Habro Woreda, Oromia, Eastern Ethiopia.Methods: A community-based cross-sectional study was conducted in Habro woreda from August 25-September 20, 2020. In total, 306 participants were included in this study, and they were approached using a systematic sampling technique. Data were collected using a pre-tested structured questionnaire through a face-to-face interview, entered into Epidata version 3.1, and analyzed using SPSS version 25. Predictors were assessed using a multivariate logistic regression analysis model and reported using an adjusted odds ratio (AOR) with a 95% confidence interval (CI). Statistical significance was set at p <0.05.Overall, the prevalence of wasting among children aged 6-59 months in the district was 28% with a 95% confidence interval [26.5, 32.2%]. Factors such as mothers unable to read and write [AOR = 3.4; 95% CI: 1.14-10.47], households without latrines [AOR = 2.91; 95% CI: 1.33-6.37], food-insecure households [AOR =4.11; 95% CI: 1.87-9], households that did not receive home visits [AOR =4.2; 95% CI: 1.92-9.15], did not eat a variety of food [AOR =7.44; 95% CI: 2.58-21.45], sick children after discharge from the program [AOR =6.55; 95% CI: 2.85-15.02], readmitted children [AOR =3.98; 95% CI: 1.43-15.07], and wasting 3.42 [AOR =3.42; 95% CI: 1.24-9.45] were factors statistically associated with outcome variables. Conclusions: This study pointed out that the prevalence of wasting among children aged 6-59 months following discharge from the Outpatient Therapeutic Program remains high. Educational status of the mother, availability of a latrine, separate kitchen, household food insecurity, household dietary diversity, home visit, and admission type were significantly associated with wasting of children after discharge from outpatient therapeutic program.